'There is still so much inside': The impact of personalised reminiscence, facilitated by a tablet device, on people living with mild to moderate dementia and their family carers. (May 2020) - Ryan, Assumpta A; McCauley, Claire O; Laird, Elizabeth A; Gibson, Aideen; Mulvenna, Maurice D; Bond, Raymond; Bunting, Brendan; Curran, Kevin; Ferry, Finola
The aim of this qualitative study was to explore the impact of a home-based, personalised reminiscence programme facilitated through an iPad app on people living with dementia and their family carers. Semi-structured interviews were used to collect data from 15 people living with dementia and 17 family carers from a region of the United Kingdom. The interviews were recorded, transcribed and analysed using thematic analysis. Six key themes emerged related to usability ('It's part of my life now'); revisiting the past ('Memories that are important to me'); home use ('It was homely'); impact on the person living with dementia ('It helped me find myself again'); gains and abilities ('There is still so much inside') and impact on relationships ('It's become very close'). These themes highlighted the impact of the reminiscence experience at an individual and relationship level for people living with dementia and their carers. The reminiscence experience also appeared to facilitate the development of new insights among participants that emphasised abilities and gains rather than disabilities and losses. The significance of personal memories was a core theme although this was not without its challenges, particularly if memories were distressing. The reminiscence experience was differentiated by individual roles. Carers tended to become more relationship-focused, whereas people living with dementia highlighted the significance of learning new skills. The study concluded that individual specific reminiscence supported by an iPad app can have a positive impact on people living with dementia and their carers at an individual and relationship level.